Pyloric reconstruction for refractory dumping syndrome after Nissen fundoplication and pyloroplasty in an infant: A case report - Younglim Kim; Suk-Bae Moon (Elsevier, 2015)
Dumping syndrome (DS) is common after gastrectomy or gastric bypass surgery, but DS in children has been described almost exclusively as a complication of Nissen fundoplication. DS resolves spontaneously in most patients; however some patients require dietary modification or medications, and surgical treatment is reserved for medically intractable cases. We herein describe an unusual case of DS in a neurologically impaired infant that developed after Nissen fundoplication and pyloroplasty and was treated by reversal of the pyloroplasty. A 12-month-old male infant was referred for medically intractable DS. He suffered from cerebral palsy and gastroesophageal reflux and underwent open Nissen fundoplication, gastrostomy tube placement, truncal vagotomy, and pyloroplasty two months before referral. Gastric emptying scintigraphy confirmed rapid gastric emptying, which was consistent with early DS. On laparotomy, a pyloroplasty scar was identified and opened along the scar. The pyloric ring was identified, reapproximated, and the incision was closed longitudinally. Postoperative gastric emptying scan showed normalized gastric emptying, and the half-emptying time was measured as 110 min. Pyloric reconstruction is a technically easy and less destructive surgery and should be considered as a therapeutic option in medically refractory DS following fundoplication and pyloroplasty.